Dél-Amerika német érdekeltségű légitársaságai – a Lufthansa leányvállalatainak rövid története 1919-1939 között - Deák, Máté (Acta Scientiarum Socialium, 2015)
German owned Airlines in South-America – The Brief History of Lufthansa’s Affiliates Between 1919–1939 Germany lost the First World War. The former winners, whose signatures are left on the pages the Versailles Treaty, have tried to deny the German naval and military aviation. France and Great Britain urged the dissolution of German military activities. The paragraphs of the Treaty of Versailles were prohibiting Germans to have the military aviation, but did not take any sanctions on the civil air activities. Sanctions of the Treaty were reflecting quite an obsolete view considering the reality of the world in the 1920s. Successful German foreign policy and their fast technical developments have given German airlines a push to start planning and executing transcontinental and after also intercontinental dimension. Lufthansa Airways has been established in 1926. Back then it was one of the largest airlines. It had been formed from „Junkers” and „Deutsche Aero Lloyd”. Nothing could proof their determination as good as Lufthansa’s Middle- and Far Eastern pioneer flights, or their ambitious expansion to the airspace of South-America and the Southern-Atlantics. German – South-American joint companies were established as SCADTA, SEDTA and CONDOR. They were operating continuously until WW II broke out.
Keywords: Lufthansa; SCADTA; CONDOR; SEDTA; Geopolicy; German Aviation; South America